1988
DOI: 10.1111/j.1600-051x.1988.tb02261.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of oral hygiene habits: a psychological approach 2‐year data

François Alcouffe

Abstract: The present communication attempts to determine the effects of individual interviews, conducted by a psychologist, on unmotivated patients' oral hygiene habits. For this investigation, 26 subjects were selected according to the following main criteria: (a) patients with good motor skills (to make sure that poor hygiene was due to poor compliance and not to poor dexterity); (b) patients suffering from periodontitis of Cl II and Cl III of the Modified Nomenclature of the American Academy of Periodontology; (c) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Our results showed that the experimental group performed better than the control group, indicating that behaviour could not be changed by educational information alone. These findings are in line with those of other studies in which the controls groups exhibited virtually no change (Alcouffe , Little et al. ) Because no confounding factors were found, meaning that the gender, the age, the number of residual tooth and the smoking status did not interfere with the level of PI before and after intervention, there should be no risk in generalizing from these results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that the experimental group performed better than the control group, indicating that behaviour could not be changed by educational information alone. These findings are in line with those of other studies in which the controls groups exhibited virtually no change (Alcouffe , Little et al. ) Because no confounding factors were found, meaning that the gender, the age, the number of residual tooth and the smoking status did not interfere with the level of PI before and after intervention, there should be no risk in generalizing from these results.…”
Section: Discussionsupporting
confidence: 92%
“…The study of addictions and tobacco habits used this kind of intervention and noted good effects on patient compliance. This type of interview seems to include principles similar to those described by Alcouffe a few years ago and applied to oral hygiene motivation (Alcouffe ). A systematic review and meta‐analysis of randomized controlled trials showed that motivational interviewing outperforms traditional advice providing (Rubak et al.…”
mentioning
confidence: 99%
“…Among the 21 selected studies, 16 were RCT [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ], and 5 were NRCTs [ 81 , 82 , 83 , 84 , 85 ] published before October 2022. The sample sizes ranged from 20 to 297 people, with follow-up intervals ranging from 1 month to 3 years.…”
Section: Resultsmentioning
confidence: 99%
“…In a long-term RCT, 26 patients were included to examine the psychological blocks of unmotivated periodontitis patients using an exploratory listening technique by a psychologist. The authors concluded that there was a significant treatment effect in the test group whose PI improved to below 50% after 1 year, whereas, in group C (control), the majority of patients remained stable or worsened [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Usually, brushing skills are acquired through parents, and it takes time to actually master them perfectly (Unkel, Fenton, Hobbs, & Frere, ). If an improper technique is detected at a later point of life, it is difficult to modify it (Alcouffe, ). Furthermore, the fine motor skills might degrade with ageing and could impair maintaining proper oral hygiene in elderly people (Felder, Reveal, Lemon, & Brown, ; Hitz Lindenmüller & Lambrecht, ).…”
Section: Introductionmentioning
confidence: 99%